I suoni attraverso lo specchio. Orizzonti coreutico-musicali di Alice - Leonardo Acone (Firenze University Press, 2017)
This essay aims at investigating the sounds and the musical spectrum contained in the two novels by Lewis Carroll. For this purpose two complementary yet dis-tinct research directions will be followed , also considering the great number of solicitations these texts offer. On one hand an analysis of music and sounds in-side the narration, identified as key elements within the relationship reali-ty/imagination , will be carried out. On the other the focus will be on those com-posers who have transformed, in the years, Alice's wonderful adventures into mu-sic masterpieces such as operas, ballets, orchestral suites and instrumental songs.